KONTRUKSI SUBJEKTIVITAS MASYARAKAT DIGITAL: ANALISIS FENOMENOLOGI TRANSENDENTAL EDMUND HUSSERL TERHADAP KONSTITUSI MAKNA DALAM ERA TEKNOLOGI - Devina Novela; Aisyah Nur; Rahma Dona (LPPM STAI Muhammadiyah Probolinggo, 2025)
The advancement of digital technology has fundamentally reshaped how individuals construct meaning, consciousness, and identity in everyday life. This study aims to analyze how digital subjectivity is constructed through the intentional relationship between consciousness and digital objects, using Edmund Husserl’s transcendental phenomenology as the analytical framework. Digital activities such as scrolling, liking, and posting are interpreted as expressions of consciousness directed toward algorithmically curated noema. Through phenomenological reflection and philosophical autoethnography, this study finds that the noesis-noema structure in digital spaces operates within a complex system of mediation, leading to a crisis of meaning, identity disorientation, and the dominance of algorithmic intentionality. Algorithms are not neutral tools but act as constitutive agents that shape the horizon of experience and consciousness. The study concludes that the digital lifeworld constitutes a new ontological landscape that demands a reflective and conscious digital epistemology, enabling individuals to reclaim autonomy in meaning-making amid accelerated and personalized information flows.